Analysis of the Impact of Magnetic Materials on Cogging Torque in Brushless DC Motor. (17th December 2021) - Karthick, K.; Ravivarman, S.; Samikannu, Ravi; Vinoth, K.; Sasikumar, Bashyam
Abstract : The cogging torque is the most significant issue in permanent magnet applications, since it has a negative impact on machine performance. In this article, the impact of magnetic materials on cogging torque is analyzed on brushless DC motors (BLDC). The effect of neodymium magnets (NdFeB), compression molded magnet, and samarium cobalt (SmCo) magnet on the cogging torque is analyzed to the BLDC motor designed for hybrid electric vehicle traction that has the peak power rating of 50 kW motor with 48 stator slots and 8 rotor poles. With the presence of these three magnetic materials, the cogging torque is estimated independently using multiposition simulation. The multiposition is simulated using a transient application that runs at constant speed. The results of cogging torque, rotational speed, angular position of BLDC motor, and magnetic flux density distribution have been presented. Also, the maximal, mean, minimal, rectified mean, and rms values of cogging torque were provided.